2021
DOI: 10.3390/ijerph18031341
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Culture and Religion on Sexual and Reproductive Health Indicators and Help-Seeking Attitudes amongst 1.5 Generation Migrants in Australia: A Quantitative Pilot Study

Abstract: In Australia, 1.5 generation migrants (those who migrated as children) often enter a new cultural and religious environment, with its own set of constructs of sexual and reproductive health (SRH), at a crucial time in their psychosexual development—puberty/adolescence. Therefore, 1.5 generation migrants may thus have to contend with constructions of SRH from at least two cultures which may be at conflict on the matter. This study was designed to investigate the role of culture and religion on sexual and reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Religion has been found to be associated with the knowledge and utilisation of sexual reproductive health services especially in Nigeria. In northern Nigeria, those who practised Islamic religion are more likely to be recalcitrant towards sexual reproductive health services, hence the reason for low/no knowledge of self-care intervention (33)(34)(35)(36). However, this study revealed that women who practise Islamic religion were more likely to use self-care practices compared to other religious a liations.…”
Section: Discussionmentioning
confidence: 99%
“…Religion has been found to be associated with the knowledge and utilisation of sexual reproductive health services especially in Nigeria. In northern Nigeria, those who practised Islamic religion are more likely to be recalcitrant towards sexual reproductive health services, hence the reason for low/no knowledge of self-care intervention (33)(34)(35)(36). However, this study revealed that women who practise Islamic religion were more likely to use self-care practices compared to other religious a liations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate that newly migrated refugees and asylum seekers seek medical help for ARD considerably more often than the nonrefugee German population. This does not necessarily reflect the burden of disease, as care-seeking behavior can be influenced not only by medical factors but also by cultural or social factors 30 , 31 . Care-seeking behavior in refugees is also influenced by the length of stay and whether a refugee is new to a facility—consultation rates were highest in the first week of stay at the refugee camp 19 .…”
Section: Discussionmentioning
confidence: 99%
“…They were allowed to one community. They communicate in their first language and live strong in their religion (29). Daniel Augenstein says that the needed tolerance may help the people to accept the Europeans' ECS Transactions, 107 (1) 6163-6174 (2022) religions and cultures.…”
Section: And Loyaltymentioning
confidence: 99%